The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1806-9061-2017-0558
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn (Crataegus Oxyacantha) Extract in the Drinking Water of Broilers on Growth and Incidence of Pulmonary Hypertension Syndrome (PHS)

Abstract: Hawthorn extract has been used for ameliorating cardiac disorders and pulmonary hypertension. Flavonoids and oligomeric proanthocyanidins are considered to be responsible for the positive health effects of hawthorn extract. The effect of Hawthorn extract in the water supply on feed intake, growth, carcass traits, internal organ weight, cardiac indices, the concentration of serum proteins and the incidence of pulmonary hypertension syndrome was evaluated in broiler chickens. At one day-of-age, 225 chickens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 21 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…16 Greater production of ROS in chickens was reported due to their susceptibility to oxidative stress. 1,2 Bioactive compounds in HFE can contribute to the protective roles against oxidative stress, lipid peroxidation and increasing activity of serum antioxidant enzymes such as glutathione peroxidase, superoxide dismutase and catalase, which counteract the oxidative stress. [4][5][6][7] So decreased in percentage of affected birds with PHS is concerned to presence of epicatechin, hyperoside, and chlorogenic acid as potent antioxidants and free radical scavenging agents to harness oxidative damages caused by PHS and other cardiovascular lesions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Greater production of ROS in chickens was reported due to their susceptibility to oxidative stress. 1,2 Bioactive compounds in HFE can contribute to the protective roles against oxidative stress, lipid peroxidation and increasing activity of serum antioxidant enzymes such as glutathione peroxidase, superoxide dismutase and catalase, which counteract the oxidative stress. [4][5][6][7] So decreased in percentage of affected birds with PHS is concerned to presence of epicatechin, hyperoside, and chlorogenic acid as potent antioxidants and free radical scavenging agents to harness oxidative damages caused by PHS and other cardiovascular lesions.…”
Section: Resultsmentioning
confidence: 99%
“…1 Also intensive genetic improvement of growth traits in broiler chickens has created a situation where the development and end size of the heart and lung is unsynchronized and leads to increasing the sensitivity of broilers to pulmonary hypertension and right ventricular failure. 2 At high altitudes with low partial oxygen pressure, the sensitivity of broilers to PHS will increase and finally leads to right ventricular failure and ascite. 3 Crataegus oxyacantha (Hawthorn) as a famous medical plant is traditionally used in treatment of cardiac diseases and cardiovascular problems.…”
Section: Introductionmentioning
confidence: 99%
“…Many plant extracts and phytochemicals do its effects by suppressing ET-1 expression and following that MMP-2 and MMP-9 expression which cause inhibition of the progression of vascular remodeling. Some of these plant extracts and phytochemicals include C. rhipidophylla, K. odoratissima, S. miltiorrhiza, T. pratense, asiaticoside, baicalin, ginsenoside Rb1, punicalagin and resveratrol; that have vascular antiremodeling effect and this way inhibit the progression of PH (Chen et al, 2003;Ahmadipour et al, 2015;He et al, 2015;Jiang and Yang, 2016;Xu et al, 2016;Ahmadipour et al, 2017;Guan et al, 2017;Hsu et al, 2018;Wang et al, 2018;Ahmadipour et al, 2019). d. Vasodilator: One of the important reasons for PH is increased blood vessel contraction and after that PH.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with C. rhipidophylla extract mix in drinking water of broiler chickens with pulmonary hypertension syndrome (PHS) induced by high altitude suggested that the extract cause an increase in albumin, globulin, food intake and body weight and a decrease in AST, ALT, ALP, and RV : TV ratio (Ahmadipour et al, 2017). ALP is one of the serum's enzymes which is a marker of liver tissue damage and the two liver enzymes, AST and ALT, increase their concentrations in oxidative stress conditions and hypoxic state before PHS.…”
Section: Crataegus Rhipidophylla Gandmentioning
confidence: 99%
See 1 more Smart Citation